1998
DOI: 10.2527/1998.76123065x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum responses to repeated sprints are affected by conditioning of horses.

Abstract: Sarcoplasmic reticulum (SR) responses to repeated sprints and to physical conditioning were studied in 10 Quarter Horses. Exercise tests (four repeated sprints on a treadmill) were conducted before and after 12 wk of sprint conditioning. Muscle samples from the middle gluteal muscle were taken before and after each exercise test, and SR vesicles were isolated. Calcium uptake was determined spectrophotometrically using antipyrylazo III, and Ca2+-ATPase activity was determined using an enzyme-linked optical assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Also, the minor differences in Ca 2+ ATPase activities at rest do not lead to the conclusion that the selection had the expected effect on SR Ca 2+ transport. This is in agreement with training experiments, showing an increased Performance but no change in Ca 2+ transport (SEMBROWICH et al, 1978;MADSEN et al, 1994;GREEN et al, 1998), but not with other investigations, indicating a reduced uptake and ATPase activity by long-term training (BELCASTRO, 1987), or an increased uptake and ATPase activity (WILSON et al, 1998), determined at rest. In agreement with the majority of investigations Ca 2+ uptake was affected by the level of exercise.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, the minor differences in Ca 2+ ATPase activities at rest do not lead to the conclusion that the selection had the expected effect on SR Ca 2+ transport. This is in agreement with training experiments, showing an increased Performance but no change in Ca 2+ transport (SEMBROWICH et al, 1978;MADSEN et al, 1994;GREEN et al, 1998), but not with other investigations, indicating a reduced uptake and ATPase activity by long-term training (BELCASTRO, 1987), or an increased uptake and ATPase activity (WILSON et al, 1998), determined at rest. In agreement with the majority of investigations Ca 2+ uptake was affected by the level of exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Endurance training of rats decreased the Ca 2+ uptake at rest (BELCASTRO, 1987) and a fibre type dependence has been shown (KIM et al, 1981). Sprint conditioning of horses increased the SR Ca 2+ uptake at rest and attenuated an exercise induced decrease in Ca 2+ transport (WILSON et al, 1998). Following endurance training of rats the Ca 2+ uptake of isolated SR was reduced, but not so in muscle homogenates (SEMBROWICH et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased density of dihydropyridine and ryanodine receptors in muscle is correlated with increased shortening velocity and force in isolated muscle (Kandarian et al, 1992;Golden et al, 2003;Mänttäri and Järvilehto, 2005), and their density is increased following endurance training in trout (Anttila et al, 2008). SERCA is responsible for calcium reuptake from the cytoplasm to the sarcoplasmic reticulum, and its activity can therefore determine muscle relaxation rate (Fleming et al, 1990;Wilson et al, 1998). SERCA activity is regulated by phosphorylation of phospholamban, which in its unphosphorylated form inhibits SERCA activity (Verboomen et al, 1992;Periasamy and Kalyanasundaram, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in horse [2, 34], human [4, 10, 15, 31], and rat [11, 28, 36] have demonstrated that exercise-induced muscle fatigue disturbs SR Ca 2+ handling properties, and the major protein responsible for Ca 2+ uptake is SR Ca 2+ -ATPase. Exercise-induced changes in Ca 2+ uptake results mainly from a shift of catalytic activity of SR Ca 2+ -ATPase [11, 17].…”
Section: Introductionmentioning
confidence: 99%